ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LAMA MENCARI KERJA BAGI TENAGA KERJA TERDIDIK DI KABUPATEN BANYUMAS - sodik Dwi purnomo; Diah Retnowati; Heris Kencana; Telefany Bunga Anugrah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of education level, parents' income, experience, training, age, gender, type of school and marital status on the length of time looking for work among educated workers in Banyumas Regency. The research sample was 100 respondents. This study uses Multiple Linear Regression analysis. The results of the study show that education has a significant negative effect on the length of job search for educated workers in Banyumas Regency. There is no difference between experience and gender and has a significant positive effect on the length of job search for educated workers in Banyumas Regency. Marital status has a significant difference and has a negative effect on the length of time looking for work for educated workers in Banyumas Regency. Parents' income, training, age and type of school have no significant effect on the length of job search for educated workers in Banyumas Regency.